Pengaruh Pemberian Sari Kacang Hijau Terhadap Kelancaran Produksi Asi Pada Ibu PostPartum - Irmawati S; Rosdiana Rosdiana (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction; Breast milk is the main source of nutrition for babies. The flow of mother's milk production can be seen from two indicators, namely mother and baby. So that the flow of mother's milk production can consume nuts, one of which is green beans. Purpose; determine the effect of intake of mung bean juice on the flow of milk production in postpartum mothers. Method; The research used is Quasi-Experimental Design with Nonequivalent Control Group Design. The number of samples in this study was 30 respondents using purposive sampling. The data collection technique was carried out by giving green beans to the respondents and then observing the flow of milk production in 1 week of intake. Data analysis using Chi-Square Test. Results; showed that giving mung bean juice 15 (50%), did not give mung bean juice 15 (50%) and showed smooth milk production (60%) while cow's milk production was not smooth (40%). The results of the analysis with a value of p = 0.009. Conclusion; that there is an effect of intake of mung bean juice on the flow of milk production in postpartum mothers. Therefore, it is recommended to postpartum mothers consume green beans, especially mung bean juice, because the more often postpartum mothers consume mung bean juice, the faster the production.